2022
DOI: 10.3390/org3010004
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of the Synthesis of Nitrofunctionalised Δ2-Pyrazolines via [3+2] Cycloaddition Reactions between α-EWG-Activated Nitroethenes and Nitrylimine TAC Systems

Abstract: We investigated the reactivity of different substituted nitrylimine-type three atom components (TACs) in [3+2] cycloaddition (32CAs) reactions with electrophilically activated nitroethenes within molecular electron density theory (MEDT). In parallel research, the molecular mechanism of the considered transformation was examined through analysis of all possible reaction channels and full optimization of all critical structures. In particular, the existence of zwitterionic intermediates on reaction paths was ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Today, numerous examples by different scientists all around the world, show that the concern of emergence of stereo impurities via the stepwise pathways for the 32CA processes is real [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]. Moreover, the accuracy of theoretical studies on the mechanism and kinetics of 32CA process have been confirmed by comparative quantum chemical investigations [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115].…”
Section: Scheme 3 the Stepwise Mechanism Through The Zwitterionic Int...mentioning
confidence: 99%
“…Today, numerous examples by different scientists all around the world, show that the concern of emergence of stereo impurities via the stepwise pathways for the 32CA processes is real [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]. Moreover, the accuracy of theoretical studies on the mechanism and kinetics of 32CA process have been confirmed by comparative quantum chemical investigations [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115].…”
Section: Scheme 3 the Stepwise Mechanism Through The Zwitterionic Int...mentioning
confidence: 99%
“…Polar processes occur between good electrophiles and good nucleophiles. According to CDFT calculations ( Table 1 ), the analyzed reactions between ( E )-3,3,3-trichloro-1-nitroprop-1-ene ( 1 ) and nitrylimines ( 2a – c ) are characterized by the major difference in their electrophilicity index (Δω > 1 eV) [ 51 , 52 ]. According to this, the presented reactions should be classified as polar processes.…”
Section: Resultsmentioning
confidence: 99%
“…The global electron density transfer (GEDT) [ 68 ] values were designated based on the formula GEDT = |ΣqA|, where qA is the net Mulliken charge and where the sum is performed over all the atoms of ( E )-3,3,3-trichloro-1-nitroprop-1-ene ( 3 ). In turn, the σ-bond development (l) indices were designated based on the formula [ 51 , 54 ]: where r TS X−Y is the distance between the reaction centers X and Y in the transition structure and where r P X−Y is the same distance in the corresponding product.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, conjugated nitroalkenes are attractive partners for three atom components (TACs) [6] in [3+2] cycloaddition (32CA) reaction. These-type transformation open a possibility of the easy construction of vide range of nitro-functionalised five-membered heterocyclic systems based on nitrile N-oxides [7], imine N-oxides [8], imine N-tiooxides [9], azometineylides [10], tiocarbonylylides [11], diazocompounds [12], azides [13] and nitrylimines [14] (Fig. 1.).…”
Section: Introductionmentioning
confidence: 99%